2015
DOI: 10.1128/iai.03129-14
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Parasitehmgb2Gene Attenuates Plasmodium berghei ANKA Pathogenicity

Abstract: h Eukaryotic high-mobility-group-box (HMGB) proteins are nuclear factors involved in chromatin remodeling and transcription regulation. When released into the extracellular milieu, HMGB1 acts as a proinflammatory cytokine that plays a central role in the pathogenesis of several immune-mediated inflammatory diseases. We found that the Plasmodium genome encodes two genuine HMGB factors, Plasmodium HMGB1 and HMGB2, that encompass, like their human counterparts, a proinflammatory domain. Given that these proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
2
14
0
2
Order By: Relevance
“…exploit the natural regulatory network of the human HMGB1 by exporting HMGB1 Pf , although, to our knowledge, experimental evidence is still lacking. Deletion of the HMGB2 homolog from Plasmodium resulted in attenuated pathogenicity in mouse models [51], indicating an involvement on severe inflammatory responses. Altogether, HMGB1 and HMGB2 appear to be involved in the inflammatory response of the host, making the HMGB family a candidate for directed inhibitory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…exploit the natural regulatory network of the human HMGB1 by exporting HMGB1 Pf , although, to our knowledge, experimental evidence is still lacking. Deletion of the HMGB2 homolog from Plasmodium resulted in attenuated pathogenicity in mouse models [51], indicating an involvement on severe inflammatory responses. Altogether, HMGB1 and HMGB2 appear to be involved in the inflammatory response of the host, making the HMGB family a candidate for directed inhibitory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Two highly pathogen parasites were used: P. berghei ANKA (PbANKA MRA-867) that kills C57Bl/6 within 7-10 days of experimental cerebral malaria (ECM) and P. berghei NK65 (PbNK65 MRA-268) that kills C57Bl/6 within 25-30 days of hyperparasitaemia and anaemia. The disruption of the hmgb2 gene in PbNK65 background was performed with 5' and 3' gene targeting KO vector designed and produced as detailed for PbANKA [18]. Wild type PbNK65 blood stages parasites were transfected using standard transfection methods [21].…”
Section: Parasitesmentioning
confidence: 99%
“…In all experiments, RBCs infected with P. berghei NK65 or its knockout counterpart Δhmgb2 PbNK65 were used to infect 5 to 10-week-old C57BL/6 mice as previously reported [18].…”
Section: Murine Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Error bars, SEM. Data are representative of three independent experiments with five mice per group; * P < 0.0095, **0.0167 < P < 0.0242, ***0.0317 < P < 0.0424, Mann-Whitney test gene, we prepared EVs from various Plasmodium parasites including two mutants for PbANKA EF-1α genes (Janse et al, 2003;line 115, eEF-1abΔ and line 118, eEF-1aa) that indeed showed no protein products as assessed by western blotting ( Figure S2b) and a PbANKA mutant where the gene encoding for the high mobility group 2 (HMGB2) protein was deleted (PbANKA hmgb2Δ), and the disruption of this gene was found previously to attenuate PbANKA pathogenicity (Briquet et al, 2015). As shown in Figure S4A, similar to hrfΔ parasites, EVs from the two lines, line 115 eEF-1ab and line 118 ΔeEF-1aa, were no longer able to inhibit the DTH response.…”
Section: Attenuation By P Berghei Irbc-derived Evs Of Antigen-specmentioning
confidence: 99%